From Youth for 74 Years of Independence of the Republic of Indonesia (Masohi Militancy: Youth Efforts to Eradicate Radicalism And Terrorism) - Marthsian Yeksi Anakotta; Hari Sutra Disemadi; Kholis Roisah (Jurnal Hukum Prasada, 2020)
Youth is an important figure of the national movement because youth are the pillars of national development and the future State of Indonesia. However, one of the problems facing Indonesia today is the involvement of youth in radicalism and terrorism. Answering this problem, this research uses normative juridical research methods with a statutory and conceptual approach. This research shows the need for the role and responsibility of youth in tackling radicalism and terrorism. The active role of youth is a reflection of moral strength, social control and agents of change in the development of the nation and the State of Indonesia, while the responsibility of youth can be carried out with masohi militancy efforts. Masohi militancy is a youth attitude that reflects resilience, enthusiasm and passion to cooperate with each other in tackling radicalism and terrorism in Indonesia which is realized through â€œPanca-Pâ€ namely Pembangunan kepemudaan, Pelayanan kepemudaan, Penyadaran pemuda, Pemberdayaan pemuda and Pengembangan pemuda (Youth Development, Youth Services, Youth Awareness, Youth Empowerment, and Youth Development).